Karies Gigi dan Status Gizi Anak - Ninna Rohmawati (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2016)
Prevalence of dental caries increase. An increase in prevalence of dental caries as a result increasing sugar consumption. This paper aims to review publish studies to khow if there was any evidence of dental caries and nutritional status of children. All paper relating to effect of dental caries and nutritional status were considered for conclution in this review. The primary focus of this paper is on dental caries problem related with nutritional status of children. Studies using cross-sectional approach. The lower index dental caries of children, so nutritional status will be getting better. Dental caries causes disruption of function of mastication that can affect nutritional intake and nutritional status.the conclusion was dental caries of children show significant relation with nutritional status.